Pelatihan Optimalisasi Website Untuk Meningkatkan Kinerja Profesional Melalui Perencanaan (Planning) Website - Eni Heni Hermaliani; Rifki Sadikin; Muhammad Haris; Mila Desi Anasanti; Waesul Bismi; Musriatun Napiah (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Al Birru Indonesia Foundation is a partner in a community service program located in the Jakasampurn area, Bekasi. This foundation is engaged in a humanitarian social institution initiated by a group of youth with their ideas and positive thoughts to build the character of an independent society, especially young teenagers. As a non-profit organization, it is very necessary to have a website that can be used as a promotional medium to introduce its programs, company profile, and as a form of accountability for the funds that have been given by donors. The current problem is that the website that is already owned is not optimal in its management, for example, related to the available menus that are still lacking and not updated. Thus, through this community service activity, training on website optimization was carried out which discussed website planning. The results of this activity were the audience of the trainees gaining knowledge and knowledge about website planning including creating page layouts, determining website facilities, display designs, mock-ups, to content structure. The results of the questionnaire showed that 60 to 70% were satisfied with the modules given and the delivery of tutors, 70% of participants stated that they were very useful for PkM activities, and 50% would participate again in the implementation of the next PkM activity.